Schiff base catalyst for copolymerization reaction of epoxide and carbon disulfide
By modifying Schiff alkaline catalysts and introducing functional groups such as methyl and fluorine, the existing catalysts have solved the problem of many by-products and low molecular weight in the CS2/epoxide copolymerization reaction, achieving higher molecular weight and purity, and improving the selectivity and activity of the catalyst.
Patent Information
- Application Number
- CN202510033184.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing zinc-coordinated Schiff base catalysts are prone to produce by-products when catalyzing the CS2/epoxide copolymerization reaction, and polymerization reaches a desired higher molecular weight for a long time, resulting in the unsatisfactory molecular weight and purity of the polycarbonate in the product.
By modifying Schiff base catalysts, different amounts of functional groups such as methyl and fluorine are introduced to enhance the selectivity of the catalyst for reaction. The specific method includes reacting 3,5 di-tert-butyl hydrocarboxylic acid with an amine reagent, then adding zinc acetate dihydrate, and reacting under specific conditions to obtain a modified catalyst.
The modification catalyst significantly improves the selectivity of copolymerization reaction between epoxide and carbon disulfide, resulting in the target polymer obtaining a higher molecular weight and a smaller dispersion coefficient, and improving the purity and performance of the product.
Smart Images

Figure CN119823364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Schiff base catalysts, and in particular to a Schiff base catalyst for copolymerization of epoxide and carbon disulfide. Background Art
[0002] Polycarbonate is a high molecular polymer containing a carbonate group. Due to its excellent thermal stability, impact resistance, creep resistance and dielectric properties, it is widely used in sealing plastic lenses, preparing high-performance optical fibers and treating wastewater containing heavy metals. It has broad application prospects and has received widespread attention from researchers. In order to further improve the solvent resistance of the material, sulfur atoms can be introduced into the polymer main chain to chemically modify it so that it has the properties of sulfur-containing compounds, giving the material good solvent resistance and oxidation resistance, thereby improving the stability of the material in application.
[0003] At present, the main processes for synthesizing polythiocarbonates include the polycondensation of acyl chloride or carbon disulfide and dithiol, the ring-opening homopolymerization of cyclic thiocarbonates, and the ring-opening copolymerization of epoxides and carbon disulfide. Among them, the preparation process of polycondensation of acyl chloride and dithiol is the most mature, but the process requires the use of highly toxic raw material phosgene, which causes harm to the environment. The copolymerization process of epoxides and carbon disulfide is to directly copolymerize thiocarbonates under the action of catalysts, which not only avoids the difficulty of preparing thiocarbonates by coupling reaction of epoxides and carbon disulfide, but also simplifies the synthesis process and reduces production costs. In addition, this process can obtain polythiocarbonate materials modified with various functional groups by chemically modifying the polymerized monomers. In 2007, Nozaki et al. used Schiff base-zinc catalyst to realize the copolymerization of cyclopropene oxide and carbon disulfide, in which the addition of chromium complex can accelerate the copolymerization reaction, and the resulting polymer has a high regioregularity. Due to its good performance in catalyzing polythiocarbonate reactions, it has been used to this day.
[0004] Zinc-coordinated Schiff base catalysts have been reported many times to have the ability to catalyze CO2 / epoxide coupling reactions. CS2 and CO2 have similar structures, so this catalyst can be used in CS2 / epoxide coupling reactions. However, this type of catalyst tends to produce more by-products when catalyzing CS2 / epoxide copolymerization, and it takes a long time for the polymerization to reach the desired higher molecular weight. Therefore, it is necessary to modify the catalyst to enhance the selectivity and activity of the catalyst for the reaction, thereby improving the molecular weight and purity of the polycarbonate in the product. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide, and introduce different numbers of methyl, fluorine and other functional groups to improve the selectivity of the catalyst for the reaction.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: Provide a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide, the general structural formula of which is:
[0007]
[0008] wherein X1 and X2 are independently MeO, Me, H or F.
[0009] Furthermore, the copolymerization of epoxide and carbon disulfide uses a Schiff base catalyst, the structural formula of which is:
[0010]
[0011]
[0012] The present invention also provides a method for preparing the Schiff base catalyst for the copolymerization reaction of epoxide and carbon disulfide, comprising the following steps:
[0013] (1) Add an anhydrous ethanol solution of 3,5-di-tert-butyl hydroxylamine to an anhydrous ethanol solution of an amine reagent, stir and reflux for 4 hours, cool to room temperature, filter, recrystallize from anhydrous ethanol, and dry under reduced pressure to obtain a precursor;
[0014] (2) Adding an ethanol solution of zinc acetate dihydrate to the ethanol solution of the precursor obtained in step (1), heating under reflux at 60° C. with stirring for 5 h under nitrogen protection, cooling to room temperature, transferring to water, extracting with dichloromethane, drying the organic phase, and then filtering, rotary evaporating, recrystallizing and filtering in sequence to obtain a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
[0015] Furthermore, in step (1), the molar ratio of 3,5-di-tert-butyl salicylic acid aldehyde to the amine reagent is 1:2.
[0016] Furthermore, in step (1), the molar concentration of the anhydrous ethanol solution of 3,5-di-tert-butyl salicylic aldehyde is 10 mmol / 20 mL.
[0017] Furthermore, in step (1), the amine reagent is o-phenylenediamine, 4-methyl o-phenylenediamine, 3,4-dimethyl substituted o-phenylenediamine, 4-fluoro o-phenylenediamine, 3,4-fluoro o-phenylenediamine or 4-ether o-phenylenediamine.
[0018] Further, the amine reagent is one of the following:
[0019]
[0020]
[0021] Furthermore, in step (2), the molar ratio of zinc acetate dihydrate to the precursor is 1:1.
[0022] Furthermore, in step (2), the molar concentration of the ethanol solution of zinc acetate dihydrate is 5 mmol / 6 mL; and the molar concentration of the ethanol solution of the precursor is 5 mmol / 12 mL.
[0023] Furthermore, in step (2), rotary evaporation is performed at 50° C. until no liquid is evaporated, and recrystallization is performed using ethanol / methylene chloride in a volume ratio of 1:1.
[0024] The present invention has the following beneficial effects:
[0025] 1. Improve the reaction selectivity of the catalyst for the copolymerization of epoxide and carbon disulfide by simply modifying the existing catalyst.
[0026] 2. By fine-tuning the catalyst modification unit, the target polymer can obtain a higher molecular weight and a smaller dispersion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the infrared spectrum of the Schiff base catalyst obtained in Example 1;
[0028] Figure 2 This is the infrared spectrum of the Schiff base catalyst obtained in Example 2;
[0029] Figure 3 This is the infrared spectrum of the Schiff base catalyst obtained in Example 3;
[0030] Figure 4 This is the infrared spectrum of the Schiff base catalyst obtained in Example 4;
[0031] Figure 5 This is the infrared spectrum of the Schiff base catalyst obtained in Example 5;
[0032] Figure 6 This is the infrared spectrum of the Schiff base catalyst obtained in Example 6. DETAILED DESCRIPTION
[0033] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0034] Example 1
[0035] A Schiff base catalyst for copolymerization of epoxide and carbon disulfide, the preparation method of which comprises the following steps:
[0036] (1) A solution of 3,5-di-tert-butyl salicylaldehyde (2.34 g, 10 mmol) in anhydrous ethanol (20 mL) was added dropwise to a solution of o-phenylenediamine (2.16 g, 20 mmol) in anhydrous ethanol, stirred and heated under reflux for 4 h, cooled to room temperature, filtered to remove the solvent, recrystallized from anhydrous ethanol, and dried under reduced pressure to obtain the precursor Salen-0 (5.26 g, 79%); the reaction process is as follows:
[0037]
[0038] (2) A solution of zinc acetate dihydrate (1.09 g, 5 mmol) in ethanol (6 mL) was added to a solution of the precursor (2.767 g, 5 mmol) obtained in step (1) in ethanol (12 mL), and the mixture was heated to reflux at 60 ° C with stirring for 5 h under nitrogen protection. The mixture was cooled to room temperature, transferred to 10 mL of water, and extracted with dichloromethane (3×100 mL). The organic phase was dried, filtered, and rotary evaporated at 50 ° C until no liquid was evaporated. The mixture was recrystallized with ethanol / dichloromethanol in a volume ratio of 1:1, and filtered to obtain Salen-ZnO (2.43 g, 81%), a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
[0039] The reaction process is:
[0040]
[0041] Example 2
[0042] A Schiff base catalyst for copolymerization of epoxide and carbon disulfide, the preparation method of which comprises the following steps:
[0043] (1) A solution of 3,5-di-tert-butyl salicylaldehyde (2.34 g, 10 mmol) in anhydrous ethanol (20 mL) was added dropwise to a solution of 4-methyl-o-phenylenediamine (2.35 g, 20 mmol) in anhydrous ethanol, stirred and heated under reflux for 4 h, cooled to room temperature, filtered to remove the solvent, recrystallized from anhydrous ethanol, and dried under reduced pressure to obtain the precursor Salen-1C (5.14 g, 73%); the reaction process is as follows:
[0044]
[0045] (2) A solution of zinc acetate dihydrate (1.09 g, 5 mmol) in ethanol (6 mL) was added to a solution of the precursor (2.91 g, 5 mmol) obtained in step (1) in ethanol (12 mL). The mixture was heated to reflux at 60 ° C. and stirred for 5 h under nitrogen protection. The mixture was cooled to room temperature, transferred to 10 mL of water, and extracted with dichloromethane (3×100 mL). The organic phase was dried, filtered, and rotary evaporated at 50 ° C. until no liquid was evaporated. The mixture was recrystallized with ethanol / dichloromethanol in a volume ratio of 1:1, filtered, and a Schiff base catalyst Salen-Zn1C (2.72 g, 86%) for the copolymerization of epoxide and carbon disulfide was obtained.
[0046] The reaction process is:
[0047]
[0048] Example 3
[0049] A Schiff base catalyst for copolymerization of epoxide and carbon disulfide, the preparation method of which comprises the following steps:
[0050] (1) A solution of 3,5-di-tert-butyl salicylaldehyde (2.34 g, 10 mmol) in anhydrous ethanol (20 mL) was added dropwise to a solution of 3,4-dimethyl-o-phenylenediamine (2.52 g, 20 mmol) in anhydrous ethanol, stirred and heated under reflux for 4 h, cooled to room temperature, filtered to remove the solvent, recrystallized from anhydrous ethanol, and dried under reduced pressure to obtain the precursor Salen-2C (6.27 g, 85%); the reaction process is as follows:
[0051]
[0052] (2) A solution of zinc acetate dihydrate (1.09 g, 5 mmol) in ethanol (6 mL) was added to a solution of the precursor (3.12 g, 5 mmol) obtained in step (1) in ethanol (12 mL), and the mixture was heated to reflux at 60° C. with stirring for 5 h under nitrogen protection. The mixture was cooled to room temperature, transferred to 10 mL of water, and extracted with dichloromethane (3×100 mL). The organic phase was dried, filtered, and rotary evaporated at 50° C. until no liquid was evaporated. The mixture was recrystallized with ethanol / dichloromethanol in a volume ratio of 1:1, and filtered to obtain Salen-Zn2C (1.98 g, 63%), a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
[0053] The reaction process is:
[0054]
[0055] Example 4
[0056] A Schiff base catalyst for copolymerization of epoxide and carbon disulfide, the preparation method of which comprises the following steps:
[0057] (1) A solution of 3,5-di-tert-butyl salicylaldehyde (2.34 g, 10 mmol) in anhydrous ethanol (20 mL) was added dropwise to a solution of 4-fluoro-o-phenylenediamine (2.21 g, 20 mmol) in anhydrous ethanol, stirred and heated under reflux for 4 h, cooled to room temperature, filtered to remove the solvent, recrystallized from anhydrous ethanol, and dried under reduced pressure to obtain the precursor Salen-1F (4.66 g, 69%); the reaction process is as follows:
[0058]
[0059] (2) A solution of zinc acetate dihydrate (1.09 g, 5 mmol) in ethanol (6 mL) was added to a solution of the precursor (2.83 g, 5 mmol) obtained in step (1) in ethanol (12 mL). The mixture was heated to reflux at 60° C. with stirring for 5 h under nitrogen protection. The mixture was cooled to room temperature, transferred to 10 mL of water, and extracted with dichloromethane (3×100 mL). The organic phase was dried, filtered, and rotary evaporated at 50° C. until no liquid was evaporated. The mixture was recrystallized with ethanol / dichloromethanol in a volume ratio of 1:1 and filtered to obtain Salen-Zn1F (2.72 g, 90%), a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
[0060] The reaction process is:
[0061]
[0062] Example 5
[0063] A Schiff base catalyst for copolymerization of epoxide and carbon disulfide, the preparation method of which comprises the following steps:
[0064] (1) A solution of 3,5-di-tert-butyl salicylaldehyde (2.34 g, 10 mmol) in anhydrous ethanol (20 mL) was added dropwise to a solution of 3,4-fluoro-o-phenylenediamine (2.32 g, 20 mmol) in anhydrous ethanol, stirred and heated under reflux for 4 h, cooled to room temperature, filtered to remove the solvent, recrystallized from anhydrous ethanol, and dried under reduced pressure to obtain the precursor Salen-2F (4.95 g, 71%); the reaction process is as follows:
[0065]
[0066] (2) A solution of zinc acetate dihydrate (1.09 g, 5 mmol) in ethanol (6 mL) was added to a solution of the precursor (2.89 g, 5 mmol) obtained in step (1) in ethanol (12 mL), and the mixture was heated to reflux at 60° C. with stirring for 5 h under nitrogen protection. The mixture was cooled to room temperature, transferred to 10 mL of water, and extracted with dichloromethane (3×100 mL). The organic phase was dried, filtered, and rotary evaporated at 50° C. until no liquid was evaporated. The mixture was recrystallized with ethanol / dichloromethanol in a volume ratio of 1:1, and filtered to obtain Salen-Zn2F (2.60 g, 86%), a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
[0067] The reaction process is:
[0068]
[0069] Example 6
[0070] A Schiff base catalyst for copolymerization of epoxide and carbon disulfide, the preparation method of which comprises the following steps:
[0071] (1) A solution of 3,5-di-tert-butyl salicylaldehyde (2.34 g, 10 mmol) in anhydrous ethanol (20 mL) was added dropwise to a solution of 4-ether o-phenylenediamine (2.68 g, 20 mmol) in anhydrous ethanol, stirred and heated under reflux for 4 h, cooled to room temperature, filtered to remove the solvent, recrystallized from anhydrous ethanol, and dried under reduced pressure to obtain the precursor Salen-1O (4.53 g, 58%); the reaction process is as follows:
[0072]
[0073] (2) A solution of zinc acetate dihydrate (1.09 g, 5 mmol) in ethanol (6 mL) was added to a solution of the precursor (3.18 g, 5 mmol) obtained in step (1) in ethanol (12 mL), and the mixture was heated to reflux at 60° C. with stirring for 5 h under nitrogen protection. The mixture was cooled to room temperature, transferred to 10 mL of water, and extracted with dichloromethane (3×100 mL). The organic phase was dried, filtered, and rotary evaporated at 50° C. until no liquid was evaporated. The mixture was recrystallized with ethanol / dichloromethanol in a volume ratio of 1:1, and filtered to obtain a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
[0074] The reaction process is:
[0075]
[0076] Test example
[0077] 1. The molecular structure of the Schiff base catalyst obtained in Examples 1-6 was determined using a Spectrum Two Fourier infrared spectrometer. Potassium bromide was used to prepare the sample. The catalyst and potassium bromide were dried in a vacuum drying oven before testing. The test results are shown in FIG. Figure 1-6 shown.
[0078] Depend on Figure 1-6 It can be seen that no 3400cm -1 The absorption peak of hydroxyl group at 1562-1531cm-1 indicates that the coordination reaction has occurred and the metal has been successfully introduced. At the same time, after the metal and ligand are coordinated, the absorption peak of C=N double bond in the ligand appears at 1562-1531cm-1. -1 The results show that Examples 1-6 all successfully prepared Schiff base catalysts.
[0079] 2. Bis(triphenylphosphorane)ammonium chloride was selected as the catalyst ligand. The commercial catalyst Salen-Cr was first used to determine the addition ratio of the catalyst and the ligand. It was found that when any of the additives or ligands were not added, the polymerization reaction could not proceed. Finally, the molar ratio of the addition amount of epoxide, carbon disulfide, catalyst and catalyst ligand was determined to be 1000:1000:1:1. The polymer quality was tested using a TP-114 electronic balance, and the polymer molecular weight and dispersity index were determined by a 1260 Infinity GPC gel permeation chromatography. The results are shown in Table 1.
[0080] The specific process is as follows: methyl 3,4-epoxycyclohexanecarboxylate (300.00 mg, 1.92 mmol) and carbon disulfide (146 mg, 1.92 mmol) are added to a 50 mL round-bottom flask containing 7 mL of toluene, and a certain proportion of catalyst Salen-ZnX and catalyst ligand bis(triphenylphosphorane)ammonium chloride are added. The reaction is refluxed at 110 ° C for 5 hours under argon protection. After the reaction is completed, it is cooled to room temperature, and methanol is poured into it to precipitate a white solid. The solid product is recrystallized using ethanol / dichloromethane with a volume ratio of 1:3, filtered with a circulating water pump, and dried under reduced pressure at 80 ° C to obtain the target polymer.
[0081] Table 1 Polymer molecular weight and dispersity index
[0082]
[0083] As shown in Table 1, compared with the commercialized catalyst Salen-Cr, when the Salen-ZnX of the present invention is used as a catalyst, the target polymer obtains a higher molecular weight and the most balanced polymer dispersity index. It is speculated that the introduction of side chains gives the catalyst molecules greater steric hindrance, reduces the molecular nucleophilicity, and increases its catalytic activity. Among them, the catalyst Salen-2F with two fluorine atoms introduced obtains the highest polymer molecular weight and the most balanced polymer dispersity index, which can be attributed to the electron-withdrawing property of the fluorine atoms, which causes a significant change in the electron cloud density of the metal center, making CHO insertion easier, thereby obtaining better catalytic activity. This result proves that the strategy of introducing different side chains in the Schiff base catalyst of the present invention can obtain a catalyst with better performance.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A Schiff base catalyst for the copolymerization of epoxide and carbon disulfide, characterized in that: Its general structural formula is: wherein X1 and X2 are independently MeO, Me, H or F.
2. The Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 1, characterized in that: Its structural formula is:
3. The method for preparing the Schiff base catalyst for the copolymerization of epoxide and carbon disulfide according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Add an anhydrous ethanol solution of 3,5-di-tert-butyl hydroxylamine to an anhydrous ethanol solution of an amine reagent, stir and reflux for 4 hours, cool to room temperature, filter, recrystallize from anhydrous ethanol, and dry under reduced pressure to obtain a precursor; (2) Adding an ethanol solution of zinc acetate dihydrate to the ethanol solution of the precursor obtained in step (1), heating under reflux at 60° C. with stirring for 5 h under nitrogen protection, cooling to room temperature, transferring to water, extracting with dichloromethane, drying the organic phase, and then filtering, rotary evaporating, recrystallizing and filtering in sequence to obtain a Schiff base catalyst for the copolymerization of epoxide and carbon disulfide.
4. The method for preparing a Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 3, characterized in that: In step (1), the molar ratio of 3,5-di-tert-butyl salicylic acid aldehyde to the amine reagent is 1:
2.
5. The method for preparing a Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 3, characterized in that: In step (1), the molar concentration of the anhydrous ethanol solution of 3,5-di-tert-butyl hydroxyethyl aldehyde is 10 mmol / 20 mL.
6. The method for preparing a Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 3, characterized in that: In step (1), the amine reagent is o-phenylenediamine, 4-methyl o-phenylenediamine, 3,4-dimethyl substituted o-phenylenediamine, 4-fluoro o-phenylenediamine, 3,4-fluoro o-phenylenediamine or 4-ether o-phenylenediamine.
7. The method for preparing a Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 3, characterized in that: In step (2), the molar ratio of zinc acetate dihydrate to the precursor is 1:
1.
8. The method for preparing a Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 3, characterized in that: In step (2), the molar concentration of the ethanol solution of zinc acetate dihydrate is 5 mmol / 6 mL; the molar concentration of the ethanol solution of the precursor is 5 mmol / 12 mL.
9. The method for preparing a Schiff base catalyst for copolymerization of epoxide and carbon disulfide according to claim 3, characterized in that: In step (2), the product is rotary evaporated at 50° C. until no liquid is evaporated, and then recrystallized using ethanol / methylene chloride in a volume ratio of 1:1.
Citation Information
Patent Citations
Trimetal Schiff base complex, preparation method thereof and application of trimetal Schiff base complex in catalyzing ring-opening copolymerization of epoxy compound
CN114853819A
Synthesis method and application of non-fullerene-based electron transport material
CN117777414A
Catalyst for synthesizing cyclic carbonate as well as preparation method and application of catalyst
CN118179610A
Improvements in the manufacture and production of dyestuffs
GB493501A
Cited By
Nano-ceramic coating for renovating galvanized guardrail steel plate coating and preparation method of nano-ceramic coating
CN121182308A